(untitled) (Linguostylistic Studies, 2014)
In the article the use of nationally marking vocabulary is analysed in texts of dramatic poems «Obsessed», «Kassandra», «In the dense forest», «On the field of blood», «Advocate Martian» and «Orgy» as a characteristic feature of idiostyle Lesia Ukrainka. On the basis of analysis of texts the thematic variety of lexical units is set with a national symbolics, that their authoress uses in a role of lingually-aesthetic signs of national culture. It is set that the names of accommodation, articles of way of life, elements of appearance, clothing and decorations, feed, labour processes and traditional for Ukrainians types of needlework, and also the names that present usually-ceremonial culture perform the duty of decoder of national mentality and sensuality related to him. Lesia Ukrainka decides the problem of reduction of sentinel-spatial distance the uses of nationally marking vocabulary between represented in texts of dramatic poems by events and reader-spectator, and also unimpeded integration of thorny philosophical problems him the intellectual-mental space. Key words: individual style, language picture of the world, mental space, semantic field, facilities of presentation of mentality, language signs of national culture. References